Influence of different seismic motion input modes on the performance of isolated structures with different seismic measures - Teng Xiaofei; Tan Ping; Liu Dewen; Zhou Linli; Jin Jianmin; Chen Huating; Liu Yanhui (Open Physics, 2020)
In order to obtain the influence of different seismic motion input modes on the performance of isolated structures with different seismic measures, the two aspects from near-fault seismic motion velocity pulse input and different dimension seismic motion input modes are studied. The finite element model of traditional seismic and base isolation frame structure with different aspect ratios is established. The actual near-seismic strong earthquake record with forward directional effect and slipping speed pulse is used as the input method of structural seismic motion to carry out nonlinear dynamics. The different dimensional seismic motion input method is selected as the quantitative, the tensile–compression stiffness ratio is the variable, and the time-history analysis of the isolation performance of a high-rise isolated structure is carried out. The experimental results show that for structures with an aspect ratio H/B of 1, 2, 3, and 4, the smaller the aspect ratio is, the better the damping effect is; the different dimensional vibration input has less isolation performance for the isolation bearing. From small to large, it is: one-dimensional vibration input, two-dimensional vibration input, three-dimensional vibration input.